Weight Cycling Increases T-Cell Accumulation in Adipose Tissue and Impairs Systemic Glucose Tolerance - Anderson, Emily K. (American Diabetes Association, 2013)
Obesity is one of the leading causes of morbidity in the U.S. Accumulation of proinflammatory immune cells in adipose tissue (AT) contributes to the development of obesity-associated disorders. Weight loss is the ideal method to counteract the negative consequences of obesity; however, losses are rarely maintained, leading to bouts of weight cycling. Fluctuations in weight have been associated with worsened metabolic and cardiovascular outcomes; yet, the mechanisms explaining this potential correlation are not known. For determination of whether weight cycling modulates AT immune cell populations, inflammation, and insulin resistance, mice were subjected to a diet-switch protocol designed to induce weight cycling. Weight-cycled mice displayed decreased systemic glucose tolerance and impaired AT insulin sensitivity when compared with mice that gained weight but did not cycle. AT macrophage number and polarization were not modulated by weight cycling. However, weight cycling did increase the number of CD4(+) and CD8(+) T cells in AT. Expression of multiple T helper 1–associated cytokines was also elevated subsequent to weight cycling. Additionally, CD8(+) effector memory T cells were present in AT of both obese and weight-cycled mice. These studies indicate that an exaggerated adaptive immune response in AT may contribute to metabolic dysfunction during weight cycling.